Capitalismo e teoria sociologica - PENDENZA, Massimo; Romania, Vincenzo; RICOTTA, Giuseppe; IANNONE, ROBERTA; Susca, Emanuela (Teorie sociologiche e trasformazioni sociali - Open Access, 2019)
For the classics, capitalism and modernity were merged. Indeed, it can be said that sociology originates precisely as a critical analysis of the processes and effects of capitalism. For the founders of the discipline, defining the theoretical and epistemological apparatus of sociology and critically analysing the origins, developments and consequences of capitalist modernity were, therefore, two sides of the same "mission". This volume takes up that mission by updating it and problematising it: by discussing classical contributions in the light of the most recent social transformations; by separating theories, processes and phenomena (from digitalisation to the transformations of work); by extending the scope of the effects of capitalism to a variety of contiguous fields.